2013
DOI: 10.1093/humrep/des448
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of preterm birth in singleton pregnancies after blastocyst versus Day 3 embryo transfer: Canadian ART Register (CARTR) analysis

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
76
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 15 publications
6
76
2
2
Order By: Relevance
“…Changes in placental morphology have also been attributed to in vitro culture of bovine embryos. Decreased villous volume density and binucleate cell volume density were found in bovine embryos cultured in vitro when compared with in vivo embryos [26]. Utsunomiya et al [27] showed a higher miscarriage rate on blastocyst transfer compared with day 3 embryo transfer and only the findings of this study were consisted with ours.…”
Section: Discussioncontrasting
confidence: 61%
“…Changes in placental morphology have also been attributed to in vitro culture of bovine embryos. Decreased villous volume density and binucleate cell volume density were found in bovine embryos cultured in vitro when compared with in vivo embryos [26]. Utsunomiya et al [27] showed a higher miscarriage rate on blastocyst transfer compared with day 3 embryo transfer and only the findings of this study were consisted with ours.…”
Section: Discussioncontrasting
confidence: 61%
“…Nonetheless, it reflected the actual situation in our centre. Blastocyst transfer is not routinely performed in out unit, because of the possible increased risk of congenital abnormalities and preterm labour, 17,18 although the pregnancy and live birth rates of the fresh cycle may be higher than those following early cleavage stage transfer. 19 The eSET policy is increasingly being applied and in a country like Belgium, the law requires eSET for all patients aged under 36 years during their first two IVF attempts.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Ahlstrom et al (28) found that conventional morphology predicts better live birth than morphokinetics (produced by TLI) after day 2 transfer. Dar et al (29) found a considerably higher risk of preterm delivery (<37 weeks) in singletons after blastocyst culture compared with cleavage stage (day 3) transfer. They proposed that extended embryo culture may have harmful effects on the resulting placentation.…”
Section: Discussionmentioning
confidence: 99%